Group B Streptococci recto-vaginal colonization, antimicrobial susceptibility pattern, and associated factors among pregnant women at selected health facilities of Wolaita Sodo Town, Southern Ethiopia - Kumalo, Abera; Gebre, Biruk; Shiferaw, Shimelis; Wolde, Wokil; Shonde, Tamirayehu (Frontiers in Microbiology, 2023)
Background: Streptococcus agalactiae or Group B Streptococcal colonization of the gastrointestinal and genital tracts of pregnant women usually remains asymptomatic; even if it is the critical determinant of infection in neonates and young infants. The aim of this study was to assess the prevalence of GBS colonization, to identify associated risk factors and antimicrobial susceptibility pattern among pregnant women at selected health facilities of Wolaita Sodo Town, Southern Ethiopia.A health facility based cross-sectional study design was conducted at WSUCSH & Wolaita Sodo Health Center from June to August, 2022. A total of 279 pregnant women who were in ANC follow up with at 35-37 weeks of gestation were included. For GBS isolation, recto-vaginal swabs were inoculated in 1ml Todd-Hewitt broth medium supplemented with 10μg/ml colistin and 15μg/ml nalidixic acid and followed by identification of isolates based on colonial morphology, gram stains, catalase reaction and CAMP tests. Antimicrobial susceptibility testing was performed using modified Kirby-Bauer disk diffusion method. All collected data were entered in Epi info 4.6.0.2, then transferred and tabulated using SPSS version 20. Logistic regression analysis was used to see the association between variables. Finally, the p-value < 0.05 were considered statistically significant.Results: In present study, 279 pregnant mothers included and their age was between 15 to 38 years with a mean of 26.5 ± 4.5 years. Of all participants, the highest 120 (43.01%) were housewives. The overall carriage rate of GBS was 67(24.0%). GBS colonization showed a statistically significant association with college and above levels of maternal education [AOR= 6.610,), P=0.01]. High susceptibility of GBS isolate was seen to Penicillin G & Chloramphenicol (92.5%) for each, Ampicillin, and Ceftriaxone (89.6%) for each, following Vancomycin (74.62%) and Erythromycin (77%). Relatively, GBS showed high resistance to Tetracycline (88%).In this study, the overall prevalence of GBS colonization was 24.0%. College and above educational level was statistically significant with GBS colonization. This study used to give attention to the management of pregnant women by making GBS culture one of the routine diagnoses during ANC follow-up and to prevent infection by early detection.